Analysis of the evidence to support the definition of Specific Protection Goals for bumble bees and solitary bees. Issue 1 (28th January 2022) - ,; Auteri, Domenica; Arce, Andres; Ingels, Brecht; Marchesi, Marco; Neri, Franco Maria; Rundlöf, Maj; Wassenberg, Jacoba
Abstract: In the context of the definition of Specific Protection Goals for bees, risk managers asked EFSA to provide the scientific background to support the decision‐making process about what needs to be protected and to what extent. In this document, information, data and tools have been investigated to support the risk managers in deciding on the Specific Protection Goals for bumble bees and solitary bees. In particular, EFSA summarised the relevant information on biology and ecology and investigated the possibility of performing an analysis of background variability to support the definition of a threshold of acceptable effects. Accounting for the current level of knowledge, EFSA concluded that this analysis is complex, and it would require information that is not yet available and tools that have not yet been fully evaluated. Nevertheless, based on the limited data available, represented by the control groups of few experimental field studies, an analysis of variability of different relevant endpoints was provided. By taking into account the results of this analysis, the biology and ecology of bumble bees and solitary bees, as well as the impact for risk assessment, EFSA illustrated possible approaches that could be followed by risk managers.